Effectiveness of the 10-valent pneumococcal conjugate vaccine against radiographic pneumonia among children in rural Bangladesh: A case-control study. Issue 42 (29th September 2020) - McCollum, Eric D.; Ahmed, Salahuddin; Roy, Arun D.; Chowdhury, Nabidul H.; Schuh, Holly B.; Rizvi, Syed J.R.; Hanif, Abu A.M.; Khan, Ahad M.; Mahmud, Arif; Pervaiz, Farhan; Harrison, Meagan; Reller, Megan E.; et al.
Abstract: Background: Pneumococcal conjugate vaccine (PCV) effectiveness against radiographic pneumonia in South Asia is unknown. Bangladesh introduced PCV10 in 2015 using a three dose primary series (3 + 0). We sought to measure PCV10 effectiveness for two or more vaccine doses on radiographic pneumonia among vaccine-eligible children in rural Bangladesh. Methods: We conducted a matched case-control study over two years from 2015 to 2017 using clinic and community controls in three subdistricts of Sylhet, Bangladesh. Cases were vaccine eligible 3–35 month olds at Upazila Health Complex outpatient clinics with World Health Organization-defined radiographic primary endpoint pneumonia (radiographic pneumonia). Clinic controls were matched to cases within a one week time window by age, sex, and clinic and had an illness unlikely to be Streptococcus pneumoniae; community controls were healthy and similarly matched within a one week time window by age and sex, and distance from the clinic. We estimated adjusted vaccine effectiveness (aVE) using conditional logistic regression. Results: We matched 1262 cases with 2707 clinic and 2461 community controls. Overall, aVE using clinic controls was 21.4% (95% confidence interval, −0.2%, 38.4%) for ≥2 PCV10 doses and among 3–11 month olds was 47.3% (10.5%, 69.0%) for three doses. aVE increased with higher numbers of doses in clinic control sets (p = 0.007). In contrast, aVE using community controls was 7.6% (95% confidence interval, −22.2%, 30.0%) for ≥2 doses. We found vaccine introduction in the study area faster and less variable than expected with 75% coverage on average, which reduced power. Information bias may also have affected community controls. Conclusions: Clinic control analyses show PCV10 prevented radiographic pneumonia in Bangladesh, especially among younger children receiving three doses. While both analyses were underpowered, community control enrollment – compared to clinic controls – was more difficult in a complex, pluralistic healthcare system. Future studies in comparable settings may consider alternative study designs.